Strategic Data Pipeline Design: Improving Operational Efficiency from Oracle to Single Storage Using Airflow S3 Data Pipeline - Debnath, Piyali (Journal of Global Economy, Business and Finance, 2025)
This paper investigates an innovative ETL pipeline managed by Apache Airflow, integrating Oracle databases with SingleStore through Amazon S3. The architecture enhances efficiency, scalability, and reliability of data integration processes. By implementing a sequence of orchestrated tasks, the study demonstrates improvements in data throughput and process automation compared to traditional ETL techniques. This article is significant as it addresses the need for scalable and efficient ETL processes in enterprise data management, demonstrating the potential improvements over traditional methods.